Experimental exhibitions and theatrical performances in Silesian post-industrial spaces - Stano, Bernadeta (Annales Universitatis Paedagogicae Cracoviensis. Studia de Arte et Educatione, 2022)
The objective of this paper is an outline of the activity of art curators, modern art representatives and theatre directors in selected examples of post-industrial space in Southern Poland – and Upper Silesia in particular. Industrial facilities provide them with both inspiration and attractive exhibition spaces. Historical buildings and their surroundings are granted new aesthetic and conceptual meanings based on the study of their history and the remembrance of their former users. They also often contribute to the revitalisation of industrial heritage